جدلية الهوية والانتماء في ادب يهود العراق في إسرائيل - جواد, فكري (lark, 2019)
Abstract:The Israeli writers of Iraqi origin were very interested in the issue of identity and belonging, and they wrote literature that embodies the strong relationship in one way or another in Iraq where their birthplace or the birthplace of their parents. It is possible to say that in many of their literary productions there are features of the problem of belonging in the annulment of their stories, which remained clinging to their original homeland, and suffered from the dispersion of identity and identity.          This research will discuss the issue of identity problem and the crisis of belonging in selected models of the literature of Iraqi Jews in Israel, selecting examples of some of the literary arts in the field of prose such as novel, story and short story, which were issued at different times. They are more than one generation. Who was born in Iraq as a story (a storm between the palm trees 1975) of the writer Sami Michael, and the novel Elie Amir (Farewell Baghdad1992) and the short story (how sat Baghdad 2008) for Almaoj Baheer. This study tries to examine the issue of the Iraqi Jewish writer's belonging to the land of his fathers and grandfathers and how the past influenced the thought of the writer, which is also fed by political and historical influences that can not be ignored. This research analyzes these literary works and uses a variety of Hebrew sources that are concerned with modern Hebrew literature and concluded with a number of important conclusions.
Keywords: Modern Hebrew literature; Jews of Iraq; Israel